A Comparison Between a Flotation Mini Pilot Plant and a Copper Concentrator Mill - K L. C Gontalves (The Australasian Institute of Mining and Metallurgy, 2005)
In 1999, the Mineral Development Centre of CVRD (CDM) acquired a flotation device referred to as Mini Pilot Plant (MPP), which is able to run continuous flotation tests with drill core samples. Since then this equipment has been used to define the flotation circuit and process conditions during the pre-feasibility phase of CVRDÆs copper sulfide projects. Until now, the MPP results had not been validated for an industrial flotation operation. The present work consists of a comparison and correlation of the results from a flotation MPP and an industrial plant. In order to make this comparison, an industrial plant was completely sampled and the feed ore was tested on bench scale and on a MPP. The metallurgical and mass balances of each test were used for the comparison.